Non-invasive and quantitative methods for assessment of blood flow in periodontal and oral soft tissues: a systematic review - Rodriguez, Amanda; Kripfgans, Oliver; Aellos, Fabiana; Velasquez, Diego; Baltazar, Alejandra; Chan, Hsun-Liang (Frontiers in Dental Medicine, 2025)
ObjectivesUnderstanding the available methods to study blood flow in the oral cavity can enhance knowledge of research methodology on periodontal circulation related to disease initiation and progression as well as wound healing. This study aims to systematically review non-invasive techniques that allow for the assessment of oral tissue perfusion in clinical and pre-clinical studies.MethodsA complete electronic literature search in 5 databases (NLM PubMed, Embase, EBSCOhost CINAHL, EBSCOhost Dentistry and Oral Sciences Source, and Wiley Cochrane Central Register of Controlled Trials) was conducted by two reviewers. The search terms included gingival blood flow, tissue perfusion, imaging perfusion, soft tissue perfusion, diagnostic, vascularization, soft tissue, and microvascularization. The focused question is: What are the available non-invasive and quantitative imaging techniques used to evaluate oral and periodontal tissue perfusion?ResultsA total of 79 articles were included for qualitative analysis. Various methods were identified, including Laser Doppler Flowmetry (LDF), Laser Speckle Contrast Imaging (LSCI), Spectral Imaging Methods (such as Diffuse Reflectance Spectroscopy), Ultrasound (US), Intravital Video Microscopy, and Oral Videocapillaroscopy. LDF is the most applied to estimate blood flow in a small focal area for the study of periodontal diseases and oral wound healing, among other indications. LSCI, providing surrogate superficial blood flow values in a 2-dimensional, larger field-of-view, has been used for similar reasons. The use of cross-sectional ultrasound is on a rise to record blood velocity and blood volume using color flow and color power modes, respectively. Comparisons of the available technologies revealed their strengths and limitations related to their spatial resolution, sensitivity, reliability, accuracy, invasiveness, dependence of (image) data in the field of view relative to probe positioning and angulation, and safety. The ideal features of such a device pertinent to probe geometry, data acquisition, recording, and infection control needs were also discussed.ConclusionsA few imaging technologies have been identified in the literature to study blood flow in the oral cavity. These methods could potentially augment our ability to diagnose oral diseases and monitor wound healing objectively and timely. In combination, these could potentially enhance treatment outcomes significantly.